(untitled) (Research, Society and Development, 2025)
Malocclusions represent one of the main oral health conditions, with functional, aesthetic, and psychosocial impacts, especially during adolescence. This study aims to compare and analyze the prevalence of malocclusions among Brazilian adolescents aged 12 and 15–19 years, based on data from the 2010 and 2023 editions of the SB Brasil Project, and to discuss the possibilities for expanding access to orthodontic treatment within the Brazilian Unified Health System (SUS). This is a descriptive study, based on secondary data extracted from the SB Brasil 2010 and 2023 reports. At age 12, a stability in the proportion of adolescents without occlusal alterations was observed, along with a reduction in defined and severe cases, but an increase in very severe cases (from 7.1% to 11.69%). In the 15–19 age group, there was an increase in the absence of malocclusions (from 65.1% to 67.1%) and a reduction in very severe cases (from 10.3% to 8.25%). Despite the stability in national indicators, regional variations reveal inequalities in access to early diagnosis and orthodontic treatment. Expanding service coverage through the Dental Specialty Centers (CEOs), with increased federal funding and triage protocols based on clinical and social criteria, is essential to ensure the principle of equity in oral health care within the SUS.